Reception and Symbolic Meaning of Salawat: A Living Hadith Study on the Religious Community in Wonokromo Pleret Bantul - Havid Nur Solikhin; Amri Saputra; Marhumah; Kadambari; Desma Hemaliyah Apita (Cultura Islamica: Journal of Islamic Studies, Management, and Culture, 2026)
This study examines the reception and symbolic meaning of 'Salawat' within the context of the A.M Assembly in Wonokromo Pleret Bantul, using the Living Hadith approach. Salawat, as one of the main practices in Islam, is not only understood as the recitation of phrases but also as an expression of love, respect, and spiritual attachment to the Prophet Muhammad (SAW). While traditional Hadith studies focus more on textual analysis, this research highlights how the Hadith regarding Salawat is understood and practiced as a living tradition within the community. This study reveals that the practice of Salawat in the A.M Assembly is more than just a theoretical or textual understanding; it is internalized and expressed through ritual actions, symbolism, and collective experience. The study also demonstrates that Salawat serves as a social and religious bond, reinforcing community cohesion and affirming ethical values among the participants. Using a field-based qualitative research method, including interviews, participatory observation, and documentation, this research investigates how the symbolic meaning of Salawat develops and resonates within the community, reflecting the dynamic integration of religious teachings within the local cultural context. This study contributes to a broader understanding of Living Hadith as a methodological approach and offers new insights into how Islamic traditions are adapted and internalized in local practices, while enriching the relevance of Hadith in contemporary religious life.